Respostas

2013-12-16T22:02:32-02:00
A) x = 2 - 1
x = 1
b) 2x - 4 = 4
2x = 4 + 4
x = 8/2
x = 4
c) 5 + x = 23
x = 23 - 5
x = 18
d) 3x + 4x +1 = 50
7x = 50 - 1
x = 49/7
x = 7
e) 6 + 4x + 2x = 42
6x = 42 - 6
x = 36/6
x = 6
f) 5x + 4 + 3x = 18
8x = 18 - 4
x  = 14/8 (simplificando)
x = 7/4
g) x + 2x - 4 = 5x + 6
3x - 4 = 5x + 6
-4 -6 = 5x - 3x
2x = -10
x = -10/2
x = -5
h) 2x - 4x + 3x = 5 - 3x - x
x = 5 - 4x
x + 4x = 5
5x = 5
x = 5/5
x = 1
i) 2(x+1) = 9
2x + 2 = 9
2x = 9 - 2
x = 7/2
j) 5(2x+1) = 4(x-1)
10x + 10 = 4x - 4
10x - 4x = -4 - 10
6x = -14
x = -14/6
x = -7/3
k) 4(x-1) = 3(x-2)
4x - 4 = 3x - 6
4x - 3x = -6 + 4
x = -2
1 3 1
A melhor resposta!
2013-12-16T22:06:10-02:00
A) x + 1 = 2
x = 2 - 1
x = 1

b) 2x - 4 = 4
2x = 4 + 4
2x = 8
x =  \frac{8}{2}
x = 4

c) 5 + x = 23
x = 23 - 5
x = 18

d) 3x + 4x + 1 = 50 
7x + 1 = 50
7x = 50 - 1
7x = 49
x = 
 \frac{49}{7}
x = 7

e) 6 + 4x + 2x = 42
6 + 6x = 42
6x = 42 - 6
6x = 36
x = 
 \frac{36}{6}
x = 6

f) 5x + 4 + 3x = 18
8x + 4 = 18
8x = 18 - 4
8x = 14
x = 
 \frac{14}{8}  
x = 1,75

g) 
x + 2x - 4 = 5x + 6
3x - 4 = 5x + 6
3x - 5x = 6 + 4
-2x = 10
x = 
 \frac{10}{-2}
x = -5  

h) 
2x - 4x + 3x = 5 - 3x - x
2x - 7x = 5 - 2x
-5x = 5 - 2x
-5x + 2x = 5
-3x = 5
x = 
 \frac{5}{-3}

i) 2 (x + 1) = 9
2x + 2 = 9
2x = 9 - 2
2x = 7
x =  \frac{7}{2}
x = 3,5

j) 5 (2x + 1) = 4 (x - 1) 
10x + 5 = 4x - 4
10x - 4x = -4 - 5
6x = -9
x = 
 \frac{-9}{6}
x = -1,5

k) 4 (x - 1) = 3 (x - 2)
4x - 4 = 3x - 6
4x - 3x = -6 + 4
x = -2
1 5 1